2023
DOI: 10.21203/rs.3.rs-3457915/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Should social withdrawal be held responsible for social media addiction? The chain mediating effect of alexithymia and negative body image

Shuang Li,
Li-li Liu,
Chongyong Sun

Abstract: To explore the influence of social withdrawal on college students' addiction to social media and its underlying mechanisms.Using the Middle School Student Social Withdrawal Questionnaire, Social Media Addiction Questionnaire, Toronto Alexithymia Scale, and Negative Body Image Scale, 2582 college students (33.46% male, average age = 19.46 years, SD = 2.23) were surveyed.Social withdrawal, alexithymia, negative body image, and social media addiction were significantly correlated with each other.Social withdrawal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This includes impairing their ability to independently select content, influencing their desires, distorting their true, practical identities, and limiting critical reflection [26]. The consequences of being addicted to SM, such as developing personal identity and image disorders [27], are more severe. Such addictions occur when individuals become dependent on seeking attention and validation, feeling a strong urge to conform to the social standards aggressively promoted on SM platforms.…”
Section: Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…This includes impairing their ability to independently select content, influencing their desires, distorting their true, practical identities, and limiting critical reflection [26]. The consequences of being addicted to SM, such as developing personal identity and image disorders [27], are more severe. Such addictions occur when individuals become dependent on seeking attention and validation, feeling a strong urge to conform to the social standards aggressively promoted on SM platforms.…”
Section: Social Mediamentioning
confidence: 99%
“…These categories refer to ASNs as applied in new social communication (33), considering the author's evaluation as a reference point (16), and acknowledging that attitudes towards ASNs is the result of socialisation (19). Personal meaningfulness is attributed to ASNs' content that exhibits coherence of scientific and routine rationality (27) and sustained interest (35) per their knowledge value. Some subjectively necessary categories were identified that vary in their level of concern with academic cognition.…”
Section: Academic Social Networkmentioning
confidence: 99%
See 1 more Smart Citation